2008
DOI: 10.1007/s11739-008-0145-z
|View full text |Cite
|
Sign up to set email alerts
|

Renal colic in Pisa emergency department: epidemiology, diagnostics and treatment patterns

Abstract: The present investigation aimed to point out some epidemiological and clinical features of renal colic in our region. All emergency department (ED) visits performed from 1 January to 31 December 2005 were reviewed to select those with diagnosis of renal colic or kidney stones. There were 70,621 visits to the University of Pisa ED. Renal colic or stone were diagnosed in 696 cases (1%); 21.6% of them were recurrent stone formers; the males to female ratio was 1.4-1. The age distribution showed a higher rate from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 16 publications
1
21
0
3
Order By: Relevance
“…2 Despite the significant increase in CT use for renal colic, there has not been a significant change in patient-centered outcomes, including hospital admissions or identification of alternate diagnoses. 3,4 Ultrasonography use in patients with suspected renal colic is common outside the United States, but CT scanning remains the first-line imaging modality for renal colic in US EDs. [5][6][7] Although consultant-performed ultrasonography may be obtained, point-of-care limited ultrasonography (PLUS) offers immediate information at the bedside and is available continuously.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…2 Despite the significant increase in CT use for renal colic, there has not been a significant change in patient-centered outcomes, including hospital admissions or identification of alternate diagnoses. 3,4 Ultrasonography use in patients with suspected renal colic is common outside the United States, but CT scanning remains the first-line imaging modality for renal colic in US EDs. [5][6][7] Although consultant-performed ultrasonography may be obtained, point-of-care limited ultrasonography (PLUS) offers immediate information at the bedside and is available continuously.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…The male to female ratio for urinary stones was 2:1, with the highest incidence in the early 50s and 60s [20,21]. In this study, males were more likely to develop urinary stones than females, but they did not differ from the other studies when compared with the average age if the rates were not so different.…”
Section: Discussionmentioning
confidence: 45%
“…In a recent Korean study, the symptoms of flank pain showed an important circadian pattern with a morning peak and an afternoon dip [12]. The time of morning peak, as reported by Cupisti and colleagues [21], was between 9 am and 12 pm. Urinary stone formation may be affected by many factors, such as stone-forming components, urinary pH, as well as inhibitors and promoters of crystallization.…”
Section: Discussionmentioning
confidence: 82%
“…In an epidemiological survey of renal colic in a large urban ED, Cupisti et al [30] find a seasonal distribution with a higher risk during summer months, particularly in July. More recently, Pincus et al [31] find that the summer rate is significantly greater than the winter rate in a large urban ED (1.53 vs. 1.24 presentations/day, rate difference 0.29, 95% confidence interval 0.15-0.43, p \ 0.001).…”
Section: Introductionmentioning
confidence: 98%